Law, Politics and the Quality of Government in Africa - Simplice Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2016)
This paper examines interconnections between law, politics and the quality of government in Africa. We investigate whether African democracies enjoy relatively better government quality compared to their counterparts with more autocratic inclinations. The empirical evidence is based on Instrumental variable Two-Stage-Least Squares and Fixed Effects with data from 38 African countries for the period 1994-2010. Political regimes of democracy, polity and autocracy are instrumented with income-levels, legal-origins, religious-dominations and press-freedom to account for government quality dynamics, of corruption-control, government-effectiveness, voice and accountability, political-stability, regulation quality and the rule of law. Findings show that democracy has an edge over autocracy while the latter and polity overlap. As a policy implication, democracy once initiated should be accelerated to edge the appeals of authoritarian regimes.
Keywords: K00; O10; P16; P43; P50; 330; Law; Politics; Democracy; Government Policy; Development